2008
DOI: 10.1017/s1461145708008894
|View full text |Cite
|
Sign up to set email alerts
|

The melanin-concentrating hormone1 receptor antagonists, SNAP-7941 and GW3430, enhance social recognition and dialysate levels of acetylcholine in the frontal cortex of rats

Abstract: Melanin-concentrating hormone (MCH)1 receptors are widely expressed in limbic structures and cortex. Their inactivation is associated with anxiolytic and antidepressive properties but little information is available concerning cognition. This issue was addressed using the selective antagonists, SNAP-7941 and GW3430, in a social recognition paradigm in rats. The muscarinic blocker, scopolamine (1.25 mg/kg s.c.), reduced social recognition, an action dose-dependently blocked by SNAP-7941 and GW3430 (0.63-10.0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 90 publications
(152 reference statements)
0
19
0
Order By: Relevance
“…The increase in the time spent in REMS and the decrease in the REMS latency during the rebound following sleep deprivation are both changes similar to those described in depression. Furthermore, the antidepressant-like profile of MCH-R1 antagonists suggest the role of MCH in the regulation of mood (Antal-Zimanyi and Khawaja 2009;Borowsky et al 2002;Chung et al 2011;Lagos et al 2011a;Millan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the time spent in REMS and the decrease in the REMS latency during the rebound following sleep deprivation are both changes similar to those described in depression. Furthermore, the antidepressant-like profile of MCH-R1 antagonists suggest the role of MCH in the regulation of mood (Antal-Zimanyi and Khawaja 2009;Borowsky et al 2002;Chung et al 2011;Lagos et al 2011a;Millan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ATC0065, ATC0175, as well as SNAP-7941, demonstrated a selective increase in swimming performance score with no change in climbing behavior (Borowsky et al 2002;Chaki et al 2005), which is similar to the actions of selective serotonin reuptake inhibitors (SSRIs; Borowsky et al 2002;Cryan et al 2005). GW3430 and GW803430 attenuated forced-swim isolation-induced aggression and marbleburying behavior in mice, another model sensitive to many clinically used antidepressants (Millan et al 2008;Gehlert et al 2009), whereas ATC0065 and ATC0175 exhibited only poor activity in marble burying (Chaki et al 2005). Contradictory findings have been reported for SNAP94847, an analog of SNAP7941; in one study, no effect was observed in forced-swim stress , whereas, in another study, it was shown to attenuate the behavioral effects in the same model (Smith et al 2009).…”
Section: Pharmacologic Evidence For the Involvement Of Mchr1 In Regulmentioning
confidence: 85%
“…MCH hippocampal microinjection was shown to increase the expression of NMDA receptor subunits and induce a consequent retrograde facilitation in rat (Varas et al 2003). Moreover, SNAP7941 and GW3430 facilitated cognition by blocking deficits in social recognition provoked either by a pronounced intersession delay or by scopolamine and by enhancing frontocortical cholinergic transmission (Millan et al 2008).…”
Section: Pharmacologic Evidence For the Involvement Of Mchr1 In Regulmentioning
confidence: 95%
See 1 more Smart Citation
“…186 -188 In addition, notwithstanding experimental evidence for a role of galanin and melanin concentrating hormone in the regulation of mood and cognition, galanin receptor ligands and melanin concentrating hormone 1 receptor antagonists are conspicuously absent from current drug pipelines-although this may be related to difficulties in finding drugs with appropriate safety and pharmacokinetic profiles, not only to the issue of efficacy. 189,190 Finally, evidence supporting the relevance of central corticotrophin releasing factor 1 (CRF 1 ) receptors in the response to stress, control of the HPA axis, regulation of mood, and induction of anxious and depressed states is overwhelming, but clinical data with selective antagonists are frustratingly sparse, and the most recent report was negative. 3,90,191,192 For these (and other) neuropeptide receptors, association with SRI properties or other mechanisms controlling depressed states should be envisaged.…”
Section: Neuropeptidergic Receptors As Targets: Focus On Neurokinin 1mentioning
confidence: 99%